Turnover of Lecanoroid Mycobionts and Their Trebouxia Photobionts Along an Elevation Gradient in Bolivia Highlights the Role of Environment in Structuring the Lichen Symbiosis - Medeiros, Ian D.; Mazur, Edyta; Miadlikowska, Jolanta; Flakus, Adam; Rodriguez-Flakus, Pamela; Pardo-De la Hoz, Carlos J.; Cieślak, Elżbieta; Śliwa, Lucyna; Lutzoni, François (Frontiers in Microbiology, 2021)
Shifts in climate along elevation gradients structure mycobiont–photobiont associations in lichens. We obtained mycobiont (lecanoroid Lecanoraceae) and photobiont (Trebouxia alga) DNA sequences from 89 lichen thalli collected in Bolivia from a ca. 4700 m elevation gradient encompassing diverse natural communities and environmental conditions. The molecular dataset included six mycobiont loci (ITS, nrLSU, mtSSU, RPB1, RPB2, and MCM7) and two photobiont loci (ITS, rbcL); we designed new primers to amplify Lecanoraceae RPB1 and RPB2 with a nested PCR approach. Mycobionts belonged to Lecanora s.lat., Bryonora, Myriolecis, Protoparmeliopsis, the “Lecanora” polytropa group, and the “L.” saligna group. All of these clades except for Lecanora s.lat. occurred only at high elevation. No single species of Lecanoraceae was present along the entire elevation gradient, and individual clades were restricted to a subset of the gradient. Most Lecanoraceae samples represent species which have not previously been sequenced. Trebouxia clade C, which has not previously been recorded in association with species of Lecanoraceae, predominates at low- to mid-elevation sites. Photobionts from Trebouxia clade I occur at the upper extent of mid-elevation forest and at some open, high-elevation sites, while Trebouxia clades A and S dominate open habitats at high elevation. We did not find Trebouxia clade D. Several putative new species were found in Trebouxia clades A, C, and I. These included one putative species in clade A associated with Myriolecis species growing on limestone at high elevation and a novel lineage sister to the rest of clade C associated with Lecanora on bark in low-elevation grassland. Three different kinds of photobiont switching were observed, with certain mycobiont species associating with Trebouxia from different major clades, species within a major clade, or haplotypes within a species. Lecanoraceae mycobionts and Trebouxia photobionts exhibit species turnover along the elevation gradient, but with each partner having a different elevation threshold at which the community shifts completely. A phylogenetically defined sampling of a single diverse family of lichen forming fungi may be sufficient to document regional patterns of Trebouxia diversity and distribution.